THE EFFECT OF E-LEARNING THROUGH THE MICROSOFT TEAMS APP IN ENGLISH SUBJECT - NAFTALIA FANY PAYUNG; NURFAIZAH SAHIB; ULFAH SYAM (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2023)
The purpose of this study was to carry out whether there was an effect of the used the Microsoft Teams application on students’ speaking skills of SMAN 18 Makassar for the 2022/2023 academic year. This study used pre-experimental methods in one pre-test and post-test class through a speaking test. The sample consisted of 25 students taken from the population of class XII Science 1 SMAN 18 Makassar for the 2022/2023 academic year. In conducting data analysis, the writers used the SPSS v.25 application. The results of the data analysis showed that there was an effect on students' speaking skills which can be seen from five speaking assessments, there are pronunciation, grammar, fluency, vocabulary, and comprehension. The average score of students increased from 47.20 on the pre-test to 84.48 on the post-test. This suggests that the H1 hypothesis is accepted and the H0 hypothesis is rejected. Based on the results of data analysis, the writers concluded that students' speech skills effect through the Microsoft Teams application.